Prestin Contributes to Membrane Compartmentalization and Is Required for Normal Innervation of Outer Hair Cells - Takahashi, Satoe; Sun, Willy; Zhou, Yingjie; Homma, Kazuaki; Kachar, Bechara; Cheatham, Mary Ann; Zheng, Jing (Frontiers in Cellular Neuroscience, 2018)
Outer hair cells (OHC) act as amplifiers and their function is modified by medial olivocochlear (MOC) efferents. The unique OHC motor protein, prestin, provides the molecular basis for somatic electromotility, which is required for sensitivity and frequency selectivity, the hallmarks of mammalian hearing. Prestin proteins are the major component of the lateral membrane of mature OHCs, which separates apical and basal domains. To investigate the contribution of prestin to this unique arrangement, we compared the distribution of membrane proteins in OHCs of wildtype (WT) and prestin-knockout (KO) mice. In WT, the apical protein PMCA2 was exclusively localized to the hair bundles, while it was also found at the lateral membrane in KOs. Similarly, a basal protein KCNQ4 did not coalesce at the base of OHCs but was widely dispersed in mice lacking prestin. Since the expression levels of PMCA2 and KCNQ4 remained unchanged in KOs, the data indicate that prestin is required for the normal distribution of apical and basal membrane proteins in OHCs. Since OHC synapses predominate in the basal subnuclear region, we also examined the synaptic architecture in prestin-KO mice. Although neurite densities were not affected, MOC efferent terminals in prestin-KO mice were no longer constrained to the basal pole as in WT. This trend was evident as early as at postnatal day 12. Furthermore, terminals were often enlarged and frequently appeared as singlets when compared to the multiple clusters of individual terminals in WT. This abnormality in MOC synaptic morphology in prestin-KO mice is similar to defects in mice lacking MOC pathway proteins such as α9/α10 nicotinic acetylcholine receptors and BK channels, indicating a role for prestin in the proper establishment of MOC synapses. To investigate the contribution of prestin’s electromotility, we also examined OHCs from a mouse model that expresses non-functional prestin (499-prestin). We found no changes in PMCA2 localization and MOC synaptic morphology in OHCs from 499-prestin mice. Taken together, these results indicate that prestin, independent of its motile function, plays an important structural role in membrane compartmentalization, which is required for the formation of normal efferent-OHC synapses in mature OHCs.